Eccentricity‐based topological invariants of tightest nonadjacently configured stable pentagonal structure of carbon nanocones. Issue 24 (25th August 2021) - Zobair, Mian Muhammad; Malik, Mehar Ali; Shaker, Hani
Abstract: Conjugated open‐ended cones in which the configured pentagons are consistent, lies in the circle of Fries Kekule structure. This nonadjacent tightest configuration of pentagons as shown in Figure 1 is consistent with a Fries Kekule structure and thus provides the most stable cone. In the study, various topological indices of the same structure in regard of physico‐concoction resources and bioactivity of substance mixtures are studied which further helps to study the behavior of chemical compounds. In this regard, Zagreb indices M 1 * G and M 2 * G of a molecular graph G is used to evaluate the complexity in chemical systems and biological organisms. In this article, we consider two complex families of stable carbon nanocones and compute their ECI, TEI, and eccentricity‐based Zagreb indices. Abstract : Carbon nanocones are funnel shaped structures made up with dominatingly from carbon with at least one dimension having micrometer or smaller scale. Nanocones are structures which have height and base of same magnitudes, this distinguish them from tipped nanowires which have longer than their diameter. Nanocones lye on the graphite surface having many applications in different fields of chemistry, especially in electron microscopy, in developing solar cells and plasma torch. In this article, we have formulated and derive closed analytical formulas for the distance‐based topological invariants such as eccentric‐connectivity index, total‐eccentricity index, and eccentricity‐based Zagreb indices of some families of nanocones discussed